Stimulus-response compatibility between stimulated eye and response location: implications for attentional accounts of the Simon effect - Valle-Inclán, Fernando; Hackley, Steven A.; de Labra, Carmen (Psychological research, 2003)
One influential theory of the Simon effect, the attention-shift hypothesis, states that attention movements are the origin of spatial stimulus codes. According to this hypothesis, stimulus-response compatibility effects should be absent when attention shifts are prevented. To test this prediction, we used monocular patches of color that required left or right key-press responses. About half of the subjects could discriminate which eye was stimulated (in a subsequent task), and showed strong spatial compatibility effects between the stimulated eye and the response location. The other half of the subjects could not make a utrocular discrimination (i.e., they could not judge which eye had received monocular stimulation), but the pattern of results was the same: the fastest reaction times were observed when the stimulated eye corresponded spatially to the required response (i.e., a Simon effect). Since the subjects presumably did not move their attention (from the subject's point of view, the stimuli were presented centrally), our results indicate that spatial codes can be produced in the absence of attention shifts. These results also show that utrocular discrimination can be assessed via indirect measures that are much more sensitive than explicit measures.